Antibacterial and wound healing properties of curcuma longa - Siti Aisyah Bt Mohd Ramli (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Wounds could become the major cause of physical disabilities. In order to heal successfully wounds must undergo several processes. However, the healing process of wound could be delayed in the presence of antimicrobial infections. Therefore, clinicians use many methods to prevent the wound infection including the use of synthetic drugs such as antibiotic and antiseptic agent. Traditional use of C. longa has mentioned its ability in wound treatment. This research was conducted to study the antimicrobial and wound healing properties of C. longa rhizomes. The extract of C. longa rhizome was prepared by using maceration method. Phytochemical test was conducted to identify the bioactive compound that exists in C. longa such as alkaloid, saponin, tannin and many more. The antibacterial properties of C. longa was studied by using disc diffusion method. The methanolic extract of the plant rhizome was tested against three types of bacteria which are Bacillus cereus, Streptococcus phyogens and Salmonella. Different concentration of extract which were 50, 100 and 200 mg/ml was used to identify the minimum inhibitory zone of the bacteria. Then, the wound healing abilities of C. longa was studied by using excision wound healing model. Excision wound healing model was conducted towards mice. The area of wound contraction was measured day by day until the wound heals completely. The tested result was compared with untreated sample to observe its effectivity to heal wound.